A review of the physiological impact of rare earth elements and their uses in biomedical Mg alloys. (August 2021) - Weng, Weijie; Biesiekierski, Arne; Li, Yuncang; Dargusch, Matthew; Wen, Cuie
Abstract: Magnesium (Mg) is well-tolerated by the body, displaying exceedingly low toxicity, rapid excretion, and numerous bioactive effects, including improved bone formation and protection against oxidative stresses; further, Mg alloys can be degraded in vivo to allow complete removal of an implant without surgical intervention, avoiding revision surgery and thrombosis concerns seen with permanent implants. Rare earth elements (REEs) have been of particular interest in alloying Mg alloys for nearly a century due to their unique chemical and physical properties but have attracted increasing attention in recent decades. The REEs contribute greatly to the mechanical and biological properties of metal alloys, and so are common in Mg alloys in a wide variety of applications; in particular, they represent the dominant alloying additions in current, clinically applied Mg alloys. Notably, the use of these elements may assist in the development of advanced Mg alloys for use as biodegradable orthopedic implants and cardiovascular stents. To this end, current research progress in this area, highlighting the physiological impact of REEs in Mg alloys, is reviewed. Clinical work and preclinical data of REE-containing Mg alloys are analyzed. The biological roles of REEs in cellular responses in vivo require further research in the development of biofunctional Mg alloy medical devices. Statement of significance: The presented work is a review into the biological impact and current application of rare-earth elements (REEs) in biodegradable Mg-based biomaterials. Despite their efficacy in improving corrosion, mechanical, and manufacturability properties of Mg alloys, the physiological effects of REEs remain poorly understood. Therefore, the present work was undertaken to both provide guidance in the development of new biomedical alloys, and highlight areas of existing concerns and unclear knowledge. Key findings of this review include a summary of current clinical and preclinical work, and the identification of Sc as the most promising REE with regards to physiological impact. Y, Ce, Pr, Gd, Dy, Yb, Sm, and Eu should be considered carefully before their use as alloying elements, with other REEs intermediate or insufficiently studied. Graphical abstract: Image, graphical abstract